Validation of a method for simultaneous analysis of cocaine, benzoylecognine and cocaethylene in urine using gas chromatography-mass spectrometry - Vinicius Stela Menotti; Deborah Thais Palma Scanferla; Kleber Ota de Oliveira; Gabriela Felber Fratucci; Gessé de Souza Alves; Erika Bando; Samuel Botião Nerilo; Magda Lúcia Félix de Oliveira; Miguel Machinski Junior; Simone Aparecida Galerani Mossini (Universidade de São Paulo, 2021)
Abstract The present study describes a method for simultaneous analysis of cocaine, benzoylecgonine and cocaethylene in urine samples. After solid phase extraction, Gas Chromatography-Mass Spectrometry was used for identification and quantification. The calibration curves were linear at 20 - 3000 ng/mL, r2 0.9997 for benzoylecgonine, 15 - 2000 ng/mL, r2 0.9985 and r2 0.9993 for cocaine and cocaethylene, respectively. Accuracy values: cocaine: 93,5 - 102,1%; benzoylecgonine: 97,5 - 104,8%; cocaethylene: 90,6 - 101,5%. Precision values: cocaine: C.V 5,4 - 14,6%; benzoylecgonine: C.V 7,8 - 12,3%; cocaethylene: C.V 5,9 - 12,3%. Detection and quantification limit values: cocaine and cocaethylene:10 ng/mL and 15 ng/mL, respectivalty; benzoylecgonine:15 ng/mL and 20 ng/mL, respectivaley. Recovery values: cocaine: 78,0 - 85,8%; benzoylecgonine: 74,0 - 79,8%; cocaethylene: 83,0 - 91,5%. The method described is advantageous compared to others, as it simultaneously detects the major analytes found in urine samples due to cocaine use and has been successfully validated.